Cu-Doped Bi2s3 Nanorod Films Via Chemical Synthesis for Improved Photoelectrochemical Water Splitting - Radhalayam, D (Elsevier B.V., 2024)
Bismuth sulfide (Bi2S3) is a promising photoelectrochemical (PEC) material due to its favorable optoelectronic properties. However, its overall PEC performance is limited by slow charge transport and high electron–hole recombination at the Bi2S3-electrolyte interface. In this study, we have intentionally introduced Cu into Bi2S3 photoelectrodes to enhance both their physical properties and PEC performance. Cu-doping concentrations ranging from 0 to 8.4 at.% were incorporated into Bi2S3 films synthesized via chemical bath deposition followed by annealing. The undoped Bi2S3 photoelectrodes exhibited nanorods with lengths of 50–100 nm, a direct bandgap of 1.26 eV, and a photocurrent density of 4.7 mA/cm2 at 1.5 V vs Hg/HgO. As the Cu-doping concentration increased from 1.0 to 4.4 at.%, the nanorod length extended to 200–400 nm, with a corresponding increase in density, leading to an enhanced photocurrent density of 6.8 mA/cm2. However, further increasing the Cu-doping concentration to 8.4 at.% resulted in a reduction in film thickness, nanorod density, and a decrease in photocurrent to 6.0 mA/cm2. These results demonstrate that Cu-doping in Bi2S3 significantly increases nanorod density and improves both the physical and PEC properties, offering a promising approach for developing more efficient PEC water-splitting devices. © 2024 Elsevier B.V.